Behavioral, environmental, and climatic factors associated with dengue hemorrhagic fever incidence in Limboto District, Gorontalo, Indonesia - Sandalayuk, Marselia; Arda, Zul Adhayani; Hanapi, Sunarti; Hafid, Wahyuni; Pakaya, Ririn; Badu, Franning Deisi; Kanan, Maria; Sandalayuk, Daud; Baba, Julfa (PT. Mega Science Indonesia, 2025)
Dengue hemorrhagic fever (DHF) remains endemic in Southeast Asia, with Indonesia reporting more than 131,000 cases and 1,135 deaths in 2022. In 2019, Gorontalo Province ranked fourth nationally in terms of incidence rate (101.53 per 100,000 population), with Gorontalo Regency accounting for 31.4% of the provincial cases in 2021. This study aimed to determine the factors associated with the incidence of dengue fever in the Limboto Health Center Working Area, Gorontalo Regency, in 2022. A cross-sectional research design was used. The research was conducted from April to July 2022 in the working area of the Limboto Health Center. The population and sample were people who lived in Limboto District, with 124 respondents. Simple random sampling was used. The independent variables were knowledge, attitude, action, water reservoir, air temperature, air humidity, and occupancy density. The dependent variable was the incidence of dengue hemorrhagic fever. The research instruments used were questionnaires, observation sheets, and hygrometers. The data were processed using univariate and bivariate analyses with SPSS at the 95% confidence level (p<0.05). Among the 124 participants, 33.1% (n=41) reported DHF infection during the study period. Chi-square analyses revealed no statistically significant associations between DHF incidence and knowledge (p=0.499, χ²=0.456), attitudes (p=0.526, χ²=0.401), preventive actions (p=1.000, χ²=0.000), water storage practices (p=0.763, χ²=0.091), ambient temperature (p=0.688, χ²=0.161), humidity (p=1.000, χ²=0.000), or household density (p=0.788, χ²=0.072). All p-values exceeded the 0.05 significance threshold, indicating insufficient evidence to reject the null hypotheses. No factors were significantly associated with DHF incidence in this cross-sectional analysis.